Surface energy for nanowire - Serghei A Baranov (Annals of Mathematics and Physics - Peertechz Publications, 2022)
The theory of surface phenomena in the production of micro-and nanocylinder for important cases is considered. Analytical solution to Gibbs-Tolman-Koenig-Buff equation for nanowire surface is given. Analytical solutions to equations for case the cylindrical surface for the linear and nonlinear Van der Waals theory are analyzed. But for a nonlinear theory, this correspondence is absent.